If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R(x) = x(95 + -4x) Multiply R * x xR = x(95 + -4x) xR = (95 * x + -4x * x) xR = (95x + -4x2) Solving xR = 95x + -4x2 Solving for variable 'x'. Reorder the terms: -95x + xR + 4x2 = 95x + -4x2 + -95x + 4x2 Reorder the terms: -95x + xR + 4x2 = 95x + -95x + -4x2 + 4x2 Combine like terms: 95x + -95x = 0 -95x + xR + 4x2 = 0 + -4x2 + 4x2 -95x + xR + 4x2 = -4x2 + 4x2 Combine like terms: -4x2 + 4x2 = 0 -95x + xR + 4x2 = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-95 + R + 4x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-95 + R + 4x)' equal to zero and attempt to solve: Simplifying -95 + R + 4x = 0 Solving -95 + R + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '95' to each side of the equation. -95 + R + 95 + 4x = 0 + 95 Reorder the terms: -95 + 95 + R + 4x = 0 + 95 Combine like terms: -95 + 95 = 0 0 + R + 4x = 0 + 95 R + 4x = 0 + 95 Combine like terms: 0 + 95 = 95 R + 4x = 95 Add '-1R' to each side of the equation. R + -1R + 4x = 95 + -1R Combine like terms: R + -1R = 0 0 + 4x = 95 + -1R 4x = 95 + -1R Divide each side by '4'. x = 23.75 + -0.25R Simplifying x = 23.75 + -0.25RSolution
x = {0, 23.75 + -0.25R}
| x^2+3x-127=0 | | 4+a-8a=-17 | | 80+95+x+38=180 | | n*6=24+n | | 13x-5x+6-2x= | | 7(-5x+5)=0 | | 90+90+128+x=180 | | 1-5x-2x=15 | | x^2+y^2+8x+4y= | | 15(3x+1)+20(3(3x+1))-5=875 | | 6x-(5x+9)=5x-29 | | 7m-20=2m | | 110+35+x+12=180 | | 8-7r+7=1 | | -6(6x-8)+5=-36x+53 | | 3k+8-k=0 | | -3y+15=2y-10 | | x^2+57x-87=0 | | 4x=-1y+20 | | 49+90+x=180 | | y=-2x^2+x | | 4b+10(b-1)= | | 5y+4=20y-26 | | -4a+a=-12 | | 25l+36=85 | | 2x+22=x+14 | | z^2-24z+144=0 | | -4(-7x+5)=148 | | 5n-7-2=11 | | 1+2x-7=-4 | | 5x-45=2x-48 | | (8x^2+1)=(12x^2+6) |